Increased Post-Hypoxic Oxidative Stress and Activation of the PERK Branch of the UPR in Trap1-Deficient Drosophila melanogaster Is Abrogated by Metformin - Alma Kokott-Vuong (MDPI AG, 2021)
Hypoxia is known to impair mitochondrial and endoplasmic reticulum (ER) homeostasis. Post-hypoxic perturbations of the ER proteostasis result in the accumulation of misfolded/unfolded proteins leading to the activation of the Unfolded Protein Response (UPR). Mitochondrial chaperone TNF receptor-associated protein 1 (TRAP1) is reported to preserve mitochondrial membrane potential and to impede reactive oxygen species (ROS) production thereby protecting cells from ER stress as well as oxidative stress. The first-line antidiabetic drug Metformin has been attributed a neuroprotective role after hypoxia. Interestingly, Metformin has been reported to rescue mitochondrial deficits in fibroblasts derived from a patient carrying a homozygous TRAP1 loss-of-function mutation. We sought to investigate a putative link between Metformin, TRAP1, and the UPR after hypoxia. We assessed post-hypoxic/reperfusion longevity, mortality, negative geotaxis, ROS production, metabolic activity, gene expression of antioxidant proteins, and activation of the UPR in Trap1-deficient flies. Following hypoxia, Trap1 deficiency caused higher mortality and greater impairments in negative geotaxis compared to controls. Similarly, post-hypoxic production of ROS and UPR activation was significantly higher in Trap1-deficient compared to control flies. Metformin counteracted the deleterious effects of hypoxia in Trap1-deficient flies but had no protective effect in wild-type flies. We provide evidence that TRAP1 is crucially involved in the post-hypoxic regulation of mitochondrial/ER stress and the activation of the UPR. Metformin appears to rescue Trap1-deficiency after hypoxia mitigating ROS production and downregulating the pro-apoptotic PERK (protein kinase R-like ER kinase) arm of the UPR.